Post-closure prostitution and the adaptation strategy of sex workers : case study of Dolly prostitution community, Surabaya Indonesia - Daulay, Pardamean; Kanto, Sanggar; Wisadirana, Darsono; Mu'adi, Sholih (Penerbit Universiti Kebangsaan Malaysia, 2018)
Closure of Dolly as the biggest prostitution industry in South East Asia since the colonial era had an impact on the loss of economic resources for prostitutes, pimps and communities surrounding the area. This action changed the social interaction through which the symbiotic mutualism between sex commercial workers, pimp, and supporting a business that has been the long-standing among the actors disappear including lifestyle of the people. Is the adaptation process of Dolly actors made public so far managed or bring them back to his former profession? Employ the qualitative method we found that three kinds of adaptation that (1) are continue doing business stealthily use social media certainly commercial sex workers and pimp, (2) follow the government program such as on job training, open small business, and joint social services program, and (3) just transform to others job that are coming back to village and open new informal business. This founding clarifies the theory of structuralism Giddens who say that people will develop suitable strategies depend on their ability in countering dominant value and powers from the powerful actors. The future research should be a focus on the issue of oppression people who powerless in the contestation proses particularly old sex commercial workers.